Sarcopenia interventions targeted at improving muscle health in adults with cancer: a systematic review and meta-analysis - Zhao, Yuan; Ying, Liying; Gao, Xiaofen; Tang, Leiwen; Zhang, Yuping; Pan, Wanya; Tian, Wenhao; Liu, Yanjie; Feng, Xiuqin (Frontiers in Nutrition, 2026)
BackgroundWhile evidence is still evolving, sarcopenia interventions show promise as supplemental treatments to mitigate cancer-related muscle loss. It is critical to distinguish this condition from age-related sarcopenia, as cancer-related muscle wasting is driven by an accelerated, multifactorial pathophysiology involving tumor-derived factors, systemic inflammation, and cancer treatments.ObjectivesWe aim to ascertain whether sarcopenia interventions are linked to improvements in muscle health among adults with cancer.MethodsWe searched seven databases from 2010 to November 2, 2025. Randomized clinical trials (RCTs) examining the relationship between sarcopenia interventions and at least one of the muscle health indicators (muscle mass, strength, physical performance) were included. We used the Cochrane Risk of Bias Tool 2 Checklist to assess the quality of the evidence. Subgroup analyses were conducted based on intervention type (exercise-only, nutrition-only, multi-component). Additionally, we performed sensitivity analyses and comprehensive publication bias assessments (Egger’s test, funnel plots, and the trim-and-fill method).ResultsFifty-nine RCTs were included. Meta-analysis showed that sarcopenia interventions were associated with statistically significant improvements in muscle mass (SMD = 0.25; 95% CI, 0.18 to 0.32), muscle strength (SMD = 0.21; 95% CI, 0.15 to 0.26), and some measures of physical performance (6-MWD: SMD = 0.28; 95% CI, 0.15 to 0.42; 30 s sit-to-stand test: SMD = 0.57; 95% CI, 0.35 to 0.78). However, interventions did not significantly improve physical performance measured by SPPB scores (SMD = 0.12; 95% CI, −0.01 to 0.26) or the 5 times chair stand test (SMD = 0.02; 95% CI, −0.15 to 0.18). Subgroup analyses suggested multi-component interventions were most beneficial for muscle mass. Publication bias was detected for some outcomes, but trim-and-fill analyses confirmed the robustness of the overall conclusions for muscle strength and physical performance.ConclusionSarcopenia interventions, particularly multi-component approaches, are associated with statistically significant, though modest, improvements in muscle health in adults with cancer. The clinical relevance of these improvements warrants further investigation. Healthcare professionals should consider integrating these interventions into care plans. Future research should focus on standardizing outcome measurements and optimizing intervention protocols to enhance clinical relevance and impact on quality of life.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, Identifier CRD420250652843.